Structural transformation of the labor force and changes in employment conditions the case of Aklan - Baco, Hazel Mae B .; Cabello, Mary Ann S. (1999.)
This paper attempts to identify trends in employment conditions and structural changes in the labor force in the province of Aklan. The trends in employment conditions and status of the labor force in Aklan is measured by five major data sets gathered from the National Statistics Office (NSO) and National Statistics Coordinating Board (NSCB). These are unemployment, underemployment and employment by economic sector, by class of workers, by major occupation group, and by major industry group., The results of this study show that Aklan remains largely agricultural and employment conditions were stagnant, but there were signs pointing to the gradual shift of economic activities from agriculture toward manufacturing and services. Empirical results are interpreted using theories of structural change. The limitations of the empirical findings owing to problems in the data set as well as the policy implications of the findings are discussed.
Thesis (Undergraduate, Bachelor of Arts in Economic-Management) University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Labor force -- Aklan; Employment -- Aklan